The Effect of Fast Food Consumption on Obesity in Teenagers : A Literature Review and Secondary Data Analysis - Indriyani; Geraldine, Keysia Feliani; Putri, Alesyia Tharfaira; Sukmariwati, Anisa; Azzahra, Siti Alya; Azzahra, Alika Fatihah; Azzahra, Nailah; Praceka, Java Ahmad Forouzan; Zaina, Ratu Faiza; Audhyanto, Claudya Valerinne; Putri, Alifa Kaliyana; Kareema, Najwa Haniah Nur; Hidayat, Yuyun (Communication In Research And Publications, 2025)
Obesity among teenagers is a growing public health concern and is often linked to the frequent consumption of fast food, which is typically high in calories, fat, and sodium, but low in dietary fiber. This study aims to explore the impact of fast food consumption on the prevalence of obesity in teenagers through a literature review and analysis of secondary data from two prior studies. A Chi-Square test was conducted to examine the relationship between the frequency of fast food intake and obesity status. The combined analysis indicates that teenagers who consume fast food more than three times per week tend to have a higher prevalence of obesity. However, statistical testing revealed that this association is not significant (Chi-Square value = 0.0145; p-value = 0.9042). These results suggest that teenage obesity is not solely influenced by fast food intake but is also affected by other factors such as physical activity, overall dietary habits, and genetic predisposition.